2018
DOI: 10.12659/msm.908172
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Renal and Hepatic Tissue-Protective Effects of N-Acetylcysteine via Ammonia Metabolism: A Prospective Randomized Study

Abstract: BackgroundThe present study sought to assess the renal and liver protective effect of N-acetylcysteine through NH3 and urea metabolism in patients with chronic obstructive pulmonary disease who were scheduled for coronary artery bypass grafting surgery.Material/MethodsPatients with chronic obstructive pulmonary disease (COPD) who were scheduled for coronary artery bypass grafting were divided into 2 groups so as to receive (Group 1, n=35) or not receive (Group 2, n=35) 900 mg/day of n-acetylcysteine for 7 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Similar work in poultry is limited. However, in mammals, NAC was demonstrated to decrease BUN and improve kidney function through regulation of ammonia and nitrogen metabolism [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Similar work in poultry is limited. However, in mammals, NAC was demonstrated to decrease BUN and improve kidney function through regulation of ammonia and nitrogen metabolism [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of similar work in poultry. NAC, but in the other hand, has been shown in mammals to improve kidney function by regulating ammonia and nitrogen metabolism [39]. NAC is an L-cysteine precursor which is used in the synthesis of reduced glutathione (GSH).…”
Section: Discussionmentioning
confidence: 99%
“…Didem Onk, et al, showed that the pretreatment by N-acetylcysteine can improve hepatic functions by regulation of the metabolism of the ammonia and nitrogen, and reduction of lactate in patients with chronic obstructive pulmonary disease who undergo coronary artery bypass grafting surgery (14).…”
Section: Discussionmentioning
confidence: 99%